A gas proportional-scintillation counter for x-ray spectrometry in the 0.1-3 keV range - Borges, F. I. G. M. (2004)
Results for the energy resolution of a uniform-field gas proportional-scintillation counter are presented for the range 0.1-3 keV. A comparison with results from the literature shows that the detector is most suitable for this energy range. Examples of x-ray fluorescence pulse-height distributions from geological and industrial samples are presented. Copyright © 2004 John Wiley & Sons, Ltd.